Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.accounts.6b00329
|View full text |Cite
|
Sign up to set email alerts
|

Nanoelectronic Heterodyne Sensor: A New Electronic Sensing Paradigm

Abstract: Nanoelectronic devices based on nanomaterials such as nanowires, carbon nanotubes, graphene, and other 2D nanomaterials offer extremely large surface-to-volume ratios, high carrier mobility, low power consumption, and high compatibility for integration with modern electronic technologies. These distinct advantages promise great potential for nanoelectronic devices as next generation chemical and biological sensors. Currently, majority of existing nanoelectronic sensors are direct current (DC) sensors, which re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 59 publications
(138 reference statements)
0
31
0
Order By: Relevance
“…22,23,112 Another example for conventional FET-sensors is that the surface layer could be modified with a biomoleculepermeable polymer layer which is proposed to operate by extending the effective distance over which charges are screened within the layer. 113 A final example of particular interest is the use of frequency-mode detection, 15,46,[114][115][116][117] where the current response is measured in the frequency domain instead of the time-domain (details can be found in ESI 6 †). The lack of wide-spread adoption of alternative operating methods may be due to: complexity, with the additional required steps required making them less commercially appealing; a lack of awareness in a rapidly changing field; or lack of reproducibility.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…22,23,112 Another example for conventional FET-sensors is that the surface layer could be modified with a biomoleculepermeable polymer layer which is proposed to operate by extending the effective distance over which charges are screened within the layer. 113 A final example of particular interest is the use of frequency-mode detection, 15,46,[114][115][116][117] where the current response is measured in the frequency domain instead of the time-domain (details can be found in ESI 6 †). The lack of wide-spread adoption of alternative operating methods may be due to: complexity, with the additional required steps required making them less commercially appealing; a lack of awareness in a rapidly changing field; or lack of reproducibility.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…Truncated antibody receptors (21) and small aptamers (22) also have been used to reduce the distance between target species and the FET surfaces, although the generality of such methods for real-time sensing in physiological conditions requires further study. In addition, recent work has shown that highfrequency mixing-based detection can be used to overcome Debye screening effects (23,24), although the device geometry may limit this approach in cellular and in vivo applications.Recently, we have developed a strategy to overcome the Debye screening limitation that involves modification of a FET sensor surface with a biomolecule-permeable polymer layer to increase the effective screening length in the region immediately adjacent to the device, and demonstrated this concept for nonspecific detection of PSA using silicon nanowire sensors in physiological solutions (25). To explore the generality of this approach for nanomaterials-based FET sensors and further extend the concept to selective analyte recognition and detection, we herein describe studies demonstrating controlled nonspecific and highly selective protein detection in physiological media using graphene FET sensors in which the device surfaces are modified only with a biomolecule-permeable polymer layer and comodified with DNA aptamer/biomolecule-permeable polymer layer, respectively.…”
mentioning
confidence: 99%
“…Truncated antibody receptors (21) and small aptamers (22) also have been used to reduce the distance between target species and the FET surfaces, although the generality of such methods for real-time sensing in physiological conditions requires further study. In addition, recent work has shown that highfrequency mixing-based detection can be used to overcome Debye screening effects (23,24), although the device geometry may limit this approach in cellular and in vivo applications.…”
mentioning
confidence: 99%
“…Since the EDL plays a crucial role in the transduction principle in FETs, it has very often been claimed that Debye screening is a limiting factor for FET‐based detection ,,. At a total ionic strength of around 0.1 M, the EDL thickness is around 1 nm, and hence it is believed that it is not possible to detect larger biomolecules such as antibody or enzyme interactions. Despite this belief, numerous examples of sensitive detection of biomolecules have been reported not only using graphene, but also with nanowires, nanotubes and organic FETs ,,.…”
Section: Fundamental Aspects Of the Graphene‐liquid Interfacementioning
confidence: 99%